Analysis of epidemiological indices of type 2 diabetes mellitus in the adult population of Moscow - Marina Fedorovna Kalashnikova; Yury Ivanovich Suntsov; Dmitriy Yur'evich Belousov; Maria Alekseevna Kantemirova (Сахарный диабет)
Diabetes mellitus is a disease that presents a global medical problem. It is necessary to implement an in-depth analysis of the epidemiological situation of type 2 diabetes mellitus for planning and organizing specialized medical help to patients with type 2 diabetes mellitus. Aim. To rate the basic epidemiological indices of type 2 diabetes mellitus in actual clinical practice using the informational database of national registry of diabetic patients. Materials and methods. Epidemiological analyses were performed in two administrative districts of Moscow. From 1999 to 2011 48978 adult patients with type 2 diabetes mellitus who were aged 18 years and older were registered. We used methods of clinical, analytical and statistical epidemiology with elements of descriptive research. Results. The prevalence rate of type 2 diabetes mellitus was 1590 per hundred thousand, most patients were in the 60?64 and 70?74 age groups, and approximately 80% of patients were older than 55 years. The morbidity rate of type 2 diabetes mellitus was 138,72 per hundred thousand and was found to be higher in women at 1,89. The mortality rate of adult patients with diabetes mellitus was 0,83, mostly in men of all ages. Cardiovascular diseases accounted for most of the registered cases of deaths (34,4%). The average life expectancy appeared to be 75,24?0,45 years, although women lived 6 years longer than men. The average duration of the disease was 10,04?0,34 years. A total of 0,4% of patients underwent hospital treatment and the average length of treatment was 17?18 days. The total number of days of disablement was an average of 307,33?30,13 days (80% of patients were older than 55 years). In the study group, a mean grade of НbА1c